Impact of the structural adjustment program on agricultural production and resource use in Egypt - Hazell, Peter B. R.; Soliman, Ibrahim; Siam, Gamal; Perez, Nicostrato D. (International Food Policy Research Institute, 1995)
This paper uses an agricultural sector model to evaluate the effects of an ambitious and ongoing policy reform program on agricultural production and resource use in Egypt. The results show that Egypt has already gained from the policy reforms, but that much larger gains depend on increased exports of high value crops. Water is found to be emerging as an important constraint on agriculture, and it will be essential to establish more effective institutional and pricing mechanisms to encourage greater water use efficiency in the future. Because many of the new lands compete with the more productive lands of the Nile delta for water, the economic return to the development of new lands is also found to be low. The policy reforms are not likely to lead to substantial increases in agricultural employment, even if exports of high value crops could be increased. However, the model results also show that more employment intensive strategies could be designed that would involve little sacrifice in economic efficiency.